Formulation and Evaluation of Bosentan Solid Dispersion - Harish, Ranga (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The therapeutic efficiency of a formulation will depend on various crucial parameters such as solubility of the drug, stability of the compound, excipients used in the formulation of finished dosage form, and the manufacturing technology used for the fabrication of finished dosage form. This research work is an attempt to enhance the solubility and dissolution rate by fabricating solid dispersion (SD) of the bosentan using hydrophilic polymers, soluplus, and kollidon VA 64. SDs of different drug: Polymer ratios were prepared using both the polymers separately (1:1, 1:2, 1:3, and 1:4). The SDs obtained were characterized by differential scanning calorimetry and X-ray powder diffraction analysis. Material and Methods: Bosentan, soluplus, and kollidon VA 64 were the important materials and hot-melt extrusion (HME) is the equipment used for manufacturing of SD. Results and Discussion: The studies shown that the crystalline drug was successfully converted to amorphous form by fabricating SD using HME. The SDs were further evaluated by performing dissolution studies, and a comparison was made between the pure drug and the SDs. The SD showing better release profile in water as dissolution medium was further evaluated. SD2 shown marked increase in the dissolution rate when compared with the pure drug dissolution. Conclusion: SD fabricated using soluplus as a polymer shown better release profile when compared with SDs fabricated with kollidon VA 64.